A10 Health Care Delivery In Huntington's Disease: An Exploratory Survey. (17th September 2014) - Rae, D; Frich, J; Roxburgh, R; Nelson, EC; Giuliano, J
Abstract : Background: In order to develop interventions and conduct studies which endeavour to improve the quality of the care provided and improve outcomes and wellbeing for individuals with HD and their families, it is crucial to establish and understand factors, structures and processes underpinning health and social care delivery at different clinics around the world. Aims: In order to gain insight into variation in current service provision across clinics/Enroll-HD research sites worldwide this survey aims to: 1) Provide a descriptive overview of how services are currently organised and delivered, 2) map and categorise models of care and interdisciplinary working in HD. Methods: All current and planned Enroll-HD sites (n = 190) were invited to participate in a structured cross-sectional survey questionnaire. To identify, define and categorise distinct models of care and service delivery, data collected will be critically evaluated using descriptive statistical methods to provide an overview of the sampled population and summarise key components of service organisation and provision. To provide further context to the data, additional free text items will be systematically analysed using qualitative methods (content analysis). Results: A descriptive overview of inter-site and inter-country differences will be presented. Conclusion: The results of this survey will provide the foundation for understanding the complexity of factors underpinning HD service delivery. The data will be used to inform development of studies within Enroll-HD to understand the determinants of good clinical care for different stages of HD.